Pengaruh Likuiditas, Ukuran Perusahaan, Leverage, dan Profitablitas terhadap Manajemen Laba - Alma Alfianti; Yulazri (Syntax Corporation, 2023)
The purpose of this research is to empirically prove the influence of Liquidity, Firm Size, Leverage, and Profitability on Earnings by using the Purposive Sampling method. While the population are pharmaceutical sector manufacturing companies that are on the list of the Indonesia Stock Exchange in 2016-2021 and have published their company's financial reports. The sample of this research is 6 companies for 6 years, so there are 36 data. This study uses panel data, namely the combination of data between cross sections and time series. For the test itself, namely with a descriptive statistical test then the classical assumption test includes the normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. According to H1 partial test results (T-Test) it shows that Liquidity (CR) has a significant effect on earnings management and has a positive direction. The results of the partial test (T-Test) H2, namely the variable firm size (FS) has a significant effect on earnings management and has a negative direction. The results of the partial test (T-Test) H3, namely the leverage variable (DER) has a significant effect on earnings management and has a positive direction. Meanwhile, the results of the partial test (T-Test) H4, namely the variable profitability (ROA) has a significant effect on earnings management and has a positive direction.